Evaluation of some biochemical and Hematological parameters for Changes Associated with Diarrhea in Calves - Zeena Ebraheem mohammed Abed; Yaser Ahmed Mowffaq Sulaiman; Hiba Younis Khalaf (Tikrit Journal of Pure Science, 2020)
This study aimed to identify the serological and hematological changes which were associated with diarrhea in calves. The study conducts on 62 calves their age range from 1 month to 6 months. The experiment started from September 2018 to March 2019. The samples consist of 42 calves with diarrhea and 20 healthy for comparison. Blood samples were taken for blood components and biochemical determination. The study showed a significant increase (p in hemoglobin, PCV and white blood cells (p . The biochemical tests showed a significant increase (p in globulin, potassium and phosphorus ions. Significant decrease (p was occurred in albumin and sodium, and no significant changes in total protein level and chloride ions concentration.